Online Social Movement: Adopsi Teknologi Informasi dalam Melakukan Gerakan Sosial di Indonesia - Ahmad Ismail; Hardiyanti Munsi; Amril Hans (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2019)
This article aims to explain whether the social movements carried out on the internet are limitedto click activism or merely mere symbolic resistance, or even beyond that? The case of the social movement raised in this study is the Akademi Berbagi Movement based on the internet, especially social media. the movement that combines online and offline gives its own nuances in doing social movements. This study used a qualitative approach with the method of connected ethnography carried out for 5 months. From the results of the research, the Akademi Berbagi Movement is one of the forms of the birth of civil society. The movement that combines online and offline has provided the context, validation and attachment of more participation by volunteers in carrying out social movements, thus giving birth to what is called 'online social movements'. This also complements the concept that Nugroho (2011) refers to as